Dampak Budaya Kerja dalam Penerapan Aplikasi E-Planning untuk Mewujudkan Good Governance - Tomi Satria Maggara; Aldri Frinaldi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
This study describes the impact of work culture in implementing the e-planning application to realize good governanc e studies in the Planning ,Research and Development Agency of 50 Kota. There search method used is descriptive qualitative, because the problems are complex so that it requires interviews and observations to get valid data. The selection of informants was carried out by using purposive sampling technique. Based on the results of the research that has been done, it can be concluded that the impact of work culture in implementing E-Planning applications to achieve Good Governance at Bapelitbang Kabupaten 50 Kota it has had a good impact but there are still some problems that the authors haveen countered, among others: there are still delays in the preparation and inp t of planning documents, there are no awards given to employees, accommodation of RPJPD programs in application E-Planning and there are still employees who don't understand how to use the E-Planning application.